Les cahiers de travail d’un traducteur : analyse d’un traduire-écrire. Donaldo Schüler traducteur de James Joyce - Paret Passos, Marie-Hélène (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2016)
I will analyse Donaldo Schüler’s 11 notebooks, where the Brazilian writer and translator, translated James Joyce’s Finnegans Wake into Portuguese. This analysis will help to bring to light the process of (re) creation of Joyce (multi) language text in Schüler’s (multi) language text. This creation goes through several work phases: reading and writing the text to be translated; pre-translating through the comments of three notebooks; preparing the first draft of the translation on seven notebooks; garnering lexical resources on a notebook. My aim is to analyse this peculiar “multi” language that makes a language-more-than-a-language. This language underlies the invention of the translator’s speech in his creation, as we can see from some notebooks, it is also apparent in the translator’s comments, that is to say, in a moment of reflexive and analytical reading and writing, that precedes the first draft of the translation. However these comments are also invention of speech, and therefore of the translator’s subjectivity. They are the expression of what I call the third degree of language. I will tackle this third degree of language focusing on Henri Meschonnic’s theories on translation.